Development Strategies for Artificial Intelligence and Robotics in Medicine - Han Xiaoguang; Zhu Xiaolong; Jiang Yuzhen; He Da; Liu Wenyong; Duan Xingguang; Tian Wei (中国工程科学, 2023)
China is facing significant challenges in healthcare owing to a severe aging population, continuously increasing healthcare demands, and uneven distribution of healthcare resources. The application of artificial intelligence (AI) and robotics in the human medical and health field can provide innovative support in theory and diagnosis for surgeons, researchers, and patients, contributing to improved clinical outcomes, reduced medical costs, and the promotion of balanced distribution of healthcare resources. This paper starts from four aspects: surgical robots, rehabilitation and nursing robots, assisted telemedicine, and medical AI, extracts the typical applications of AI and robots in the medical field, assesses the current status of AI and robotics in medicine, and evaluates pertinent policies, laws, and regulatory frameworks. Based on the understanding of the challenges faced in the development of AI and robotics in medicine in China, it delineates phased  development goals and identifies future key directions: advancing toward differentiated, miniaturized, and intelligent surgical robotics; emphasizing patient-centered rehabilitation and nursing robotics; achieving multi-tasking and high situational awareness in assisted  telemedicine; and promoting medical AI for healthcare innovation. This paper suggests determining promising research directions for surgical robotics, promoting domestic production of core components, exploring commercially viable models that align with national conditions,  expanding the coverage of product applications, focusing on the development of specialized talent pools, implementing technology innovation driven by clinical demands, and strengthening regulations to reduce medical accidents and safeguard data privacy. These measures are expected to foster high-quality development of AI and robotics in medicine in China.